2011
DOI: 10.1029/2011ja016998
|View full text |Cite
|
Sign up to set email alerts
|

Responses of equatorialFregion to different geomagnetic storms observed by GPS in the African sector

Abstract: This article presents the first results regarding the investigation of the response of the equatorial ionospheric F region in the African sector during geomagnetic storm periods between April 2000 and November 2007 using GPS‐derived vertical total electron content observed at Libreville, Gabon (0.35°N, 9.67°E, dip latitude −8.05°S). We performed a superposed epoch analysis of the storms by defining the start time of the epoch as the storm onset time. During geomagnetic storms, the altered electric fields contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…P ionospheric storm effects were more prevalent over low‐latitude stations, which is in accordance to the previous studies (e.g., Adeniyi, ; Adewale et al, ; Prölss, ). The local daytime P ionospheric storm effects can occur either due to the daytime eastward PPEFs or the mechanical effects of storm time equatorward neutral winds and surges alone.…”
Section: Overall Statisticssupporting
confidence: 92%
See 2 more Smart Citations
“…P ionospheric storm effects were more prevalent over low‐latitude stations, which is in accordance to the previous studies (e.g., Adeniyi, ; Adewale et al, ; Prölss, ). The local daytime P ionospheric storm effects can occur either due to the daytime eastward PPEFs or the mechanical effects of storm time equatorward neutral winds and surges alone.…”
Section: Overall Statisticssupporting
confidence: 92%
“…N ionospheric storm effects were observed during both CME‐ and CIR‐driven storms over low‐latitude stations (MBAR and SHEB). N ionospheric storm effects over the low latitude could be due to DDEF produced by the thermospheric disturbance winds (Abdu et al, ; Adewale et al, ; Blanc & Richmond, ; Fejer & Emmert, ; Kuai et al, ; Pincheira et al, ). During Joule heating and particle precipitation at high latitudes, thermospheric heating sets pressure gradient forces that produces disturbances in thermospheric winds (Pincheira et al, ).…”
Section: Overall Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…First statistical results into equatorial ionospheric response over the African sector for a number of geomagnetic storms during the period April 2000-November 2007 over Libreville (0. 361N, 9.671E), Gabon indicated positive and negative storm effects in every storm period (Adewale et al, 2011). This study further revealed that positive storm effects occur more frequently than negative storm effects and generally last longer irrespective of storm onset times.…”
Section: Introductionmentioning
confidence: 86%
“…In Africa, limited studies (e.g. Fayose et al, 2012;Adewale et al, 2011;Ouattara and Fleury, 2011;Okonkwo and Ugwuanyi, 2012;Zoundi et al, 2012;D'ujanga et al, 2012;Oron et al, 2013 etc) were carried out to understand its ionospheric phenomena and irregularities showed a significant diurnal and seasonal TEC variations. The highest day-to-day TEC values were observed around 18:00 UT and highest seasonal values exhibited during equinoctial months, moderate in the summer solstice and least in the winter solstice.…”
Section: Introductionmentioning
confidence: 98%